How research positions Central and Eastern European women entrepreneurs: A 30-year discourse analysis. Issue 3 (15th March 2023) - Rugina, Sanita; Ahl, Helene
ABSTRACT: This paper analyses how research on women's entrepreneurship conducted in Central and Eastern Europe (CEE) constructs and positions women entrepreneurs. Entrepreneurship was illegal under the socialist regimes that governed this area and only began to develop after independence was obtained in the early 1990s. Consequently, research on entrepreneurship, including women's entrepreneurship, is somewhat new to the region. Our discourse analysis of existing research in this area reveals that, despite different historical pathways towards entrepreneurship, normative premises that exist in Western studies on women's entrepreneurship also prevail in scholarship produced in CEE. These normative premises impose dominant constructs and methodologies on entrepreneurship policy and the scholarly community. The discourse analysis identified five positioning constructs of women entrepreneurs, all of which stem from the assumption that women are (essentially) inadequately equipped for entrepreneurship. We discuss the discursive practices that produce these results and suggest ways forward for research on women's entrepreneurship in CEE.